2022
DOI: 10.3390/vetsci9020057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Seroprevalence and Associated Risk Factors for Anaplasmosis in Camelus dromedarius

Abstract: (1) Background: Anaplasmosis is an infectious disease in camels caused by an obligate intracellular bacterium that is transmitted by ticks. (2) Methods: A cross-sectional study was conducted during 2020 to study the seroprevalence of Anaplasma spp. among Camelus dromedarius in three governorates in Egypt and assess the associated risk factors. Serum samples from 365 camels were examined by a competitive enzyme-linked immunosorbent assay (cELISA) test. (3) Results: Overall, the seroprevalence of anaplasmosis am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Ticks are obligate hematophagous ectoparasites of humans and animals. They transmit more species of pathogens than any other blood-feeding arthropod [ 1 - 6 ] and require careful monitoring and control measures [ 7 , 8 ]. A variety of tick-borne diseases affect animal productivity in developing countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ticks are obligate hematophagous ectoparasites of humans and animals. They transmit more species of pathogens than any other blood-feeding arthropod [ 1 - 6 ] and require careful monitoring and control measures [ 7 , 8 ]. A variety of tick-borne diseases affect animal productivity in developing countries [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, significant association of seropositivity with camel age was not found for Anaplasma spp. in Egypt [ 39 ], or C. burnetii in Algeria [ 40 ], although in both studies camels over 15 years of age were not considered separately. The ability of older camels to mount a serological response to tick-associated infections and the persistence of serum antibodies in such older animals deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…Anaplasmosis is a tick-borne disease that affects various domestic ruminants, including sheep and goats, and is widely distributed in tropical and subtropical regions [ 2 - 4 ]. In Egypt, despite the detection of Anaplasma spp.…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, few studies have been reported for Anaplasma spp. in cattle, buffalo, and camels [ 2 , 3 ]. At present, no research has investigated Anaplasma spp.…”
Section: Introductionmentioning
confidence: 99%